Complete Basic Immunization Status of 12 Months Babies at West Wonggeduku Health Center Based on the Health Belief Model - Arista, Bela; Tasnim, Tasnim; Amraeni, Yunita (Waluya The International Science of Health Journal, 2024)
Introduction: From the initial interviews conducted by three mothers, they said that health workers had never conducted outreach to the public about the importance of immunization and the negative impact on the baby's condition if they were not fully immunized, so each region needed to study the factors that influence this. Implementation of immunizations including in the West Wonggeduku Community Health Center area. Method: The type of research sample in this study is quantitative research using a cross sectional study approach which aims to determine the relationship between the complete basic immunization status of 12 Month old babies based on the health belief model theory at the West Wonggeduku Community Health Center in 2022. The population is 120 people, with a sample of 92 people. The sampling technique in this research used the Simple Random Sampling technique, using the Chi-Square Statistical test. Results: Research shows that there is a relationship between perception susceptibility to the completeness of complete basic immunization status X2 count = 34.389, X2 table value = 3.841, and Phi value = 0.611 Conclusion: The results of this research are that there is a relationship between perception susceptibility and completeness of immunization in 12 Month old babies